1993
DOI: 10.1042/bj2930835
|View full text |Cite
|
Sign up to set email alerts
|

Signalling through CD28 T-cell activation pathway involves an inositol phospholipid-specific phospholipase C activity

Abstract: Stimulation of the human T-cell line, Jurkat, by a monoclonal antibody (mAb) directed against the CD28 molecule leads to sustained increases in intracellular levels of Ca2+ ([Ca2+]i); the initial rise in Ca2+ comes from internal stores, followed by Ca2+ entry into the cells. The CD28 molecule also appears to activate polyphosphoinositide (InsPL)-specific phospholipase C (PLC) activity in Jurkat cells, as demonstrated by PtdInsP2 breakdown, InsP3 and 1,2-diacylglycerol generation and PtdIns resynthesis. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…DISCUSSION A major challenge in the study of CD28 signalling is the lack of a detectable response with the treatment of soluble bivalent anti-CD28 alone (reviewed in references 26 and 34). No calcium flux, inositol phosphate release, or significant tyrosine kinase activity occurs unless CD28 is super-cross-linked (31,42,43). Although a direct study of CD28 signalling has not been possible, two distinct events stimulated by CD28 ligation can be detected in the presence of a primary signal such as PMA: the tyrosine phosphorylation of several proteins (36,57) and the induction of the CD28RC in the nucleus (14,58).…”
Section: Resultsmentioning
confidence: 99%
“…DISCUSSION A major challenge in the study of CD28 signalling is the lack of a detectable response with the treatment of soluble bivalent anti-CD28 alone (reviewed in references 26 and 34). No calcium flux, inositol phosphate release, or significant tyrosine kinase activity occurs unless CD28 is super-cross-linked (31,42,43). Although a direct study of CD28 signalling has not been possible, two distinct events stimulated by CD28 ligation can be detected in the presence of a primary signal such as PMA: the tyrosine phosphorylation of several proteins (36,57) and the induction of the CD28RC in the nucleus (14,58).…”
Section: Resultsmentioning
confidence: 99%
“…Triggering of the CD28 receptor with antibodies induces phospholipase C and Ras activation (18,19). Previous studies using CD28 antibodies have suggested that PTKs involved in CD28 signal transduction include the Src kinases p56 lck and p59 fyn (20,21) and the Tec family kinase ITK/EMT (22).…”
mentioning
confidence: 99%
“…To demonstrate that PRRIV can specifically respond to CD28 downstream signals, we used the CD28-deficient mutant Jurkat T-cell clone, JF3. As the JH6.2 subclone, JF3 was selected by limiting dilution of Jurkat JA3.52 T cells (43). We used RT-PCR to control for the lack of CD28 expression in the JF3 subclone.…”
Section: Resultsmentioning
confidence: 99%